Sob a ótica das crianças: cultura de mídia na educação infantil e as representações de gênero em desenhos animados - Sabrina de Sousa Soares (2020)
The cartoon animations, especially because of its ludic and fantastic formats, are one of the most important media artefacts directed to kids. Through a research involving kids between four and five years old from an Early Childhood School in the city of Belo Horizonte, this study tried to understand the meanings the kids have been giving to feminine and masculine traits shown by them in their interactions when they express how they comprehend and perform the gender relations lived by them, and how these ideas are marked by the content and the characters of cartoon animations. The research is composed by a multidisciplinary theoretical referential that integrates areas such as studies about early childhood, and studies on culture and gender, from post-structuralist approaches. The methodology used in this research incorporated ethnographic guiding principles, making use of observation of participants and a field research diary to record the spontaneous relations between the kids. The results indicate that gender acquires materiality in the bodies in which, performatically, make explicit the symbolic and corporal dimensions associated to the masculine and to the feminine. It is important to point out that, in this sense, the kids, relying on the gender norms, modalize performatically their identities in a dynamics in which the cartoon animations can both provide the elements that delimitate the outline of femininities and masculinities, endorsing the gender boundaries between girls and boys, and also provide breaches and gaps to the development and resignification of these boundaries. The kids, as active spectators, demonstrate that gender is also learnt through cartoon animations as well. As an educative resource, we have produced a short-movie animation (animatic) directed to toddlers. The movie, called Léxicon Júpiter in: an episode on the Moon, was elaborated based on the results of the research and search, based on the representation of the heroic characters, to challenge certain predominating masculine and feminine references in the construction of super-heroes that are ubiquitous in the cartoon animations universe. Léxicon Júpiter is a female character, strong and super speedy. Her corporal representation rejects erotizing and hypersexualizing marks that are commonly associated to female heroism in the contemporary cultural productions.